PARTNERSHIP STRATEGY IN THE DEVELOPMENT OF THE HALAL INDUSTRY BASED ON LOCAL WISDOM FROM THE PERSPECTIVE OF SHARIA COMPLIANCE - Irma Martawati; Kamiruddin Kamiruddin; Muhammad Fakhri Amir (Universitas Nusa Cendana, 2026)
This study aims to analyze partnership strategies, challenges, and obstacles in developing a halal industry grounded in local wisdom and sharia compliance principles. The research employs a qualitative design with a phenomenological approach, focusing on understanding the lived experiences and perspectives of business actors in implementing partnership strategies. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that partnership strategies in developing the halal industry include: (a) enhancing the knowledge and skills of business actors, (b) involving local farmers in the supply chain, (c) increasing the number of employees, (d) expanding business networks, (e) broadening marketing channels, (f) fostering collaboration with relevant stakeholders, and (g) strengthening competitiveness. However, several challenges were identified, including limited availability of raw materials, the absence of halal certification, and the lack of formal partnership agreements. In addition, key obstacles consist of: (a) rapid technological changes, (b) limited understanding among farmers regarding raw material quality standards, (c) difficulty in recruiting skilled workers, (d) limited business networks or relationships, (e) minimal promotional budgets—particularly for digital marketing, (f) ego or individualistic attitudes among stakeholders, and (g) insufficient innovation. From a sharia compliance perspective, halal industry development must avoid practices such as maisir, tadlis, gharar, haram, riba, ihtikar, and bathil. Keywords: Partnership Strategy; Local-Based Halal Industry Development; Sharia Compliance